IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE AND DIGITAL MARKETING ON MILLENNIALS' PURCHASE INTENTION ON THE TIKTOK SHOP PLATFORM THROUGH E-WOM AS A MEDIATING VARIABLE - Nargis Jihan Pratami Bantam; Raden Ayu Aisah Asnawi; Victor Ernest Huwae (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the impact of Artificial Intelligence (AI) and Digital Marketing (DM) on Purchase Intention (PI) among millennial consumers on TikTok Shop, with Electronic Word-of-Mouth (e-WOM) as a mediating variable. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), this research empirically validates the relationships between AI, DM, e-WOM, and PI. The findings indicate that AI-driven personalization and DM strategies significantly influence e-WOM, which in turn enhances PI. AI applications, such as chatbots and personalized recommendations, improve consumer engagement, prompting them to share positive experiences through e-WOM. Similarly, DM strategies, including influencer marketing and interactive social media campaigns, increase consumer discussions and brand credibility, strengthening e-WOM’s role as a persuasive mechanism. The mediation analysis confirms that e-WOM serves as a crucial intermediary, bridging the gap between AI, DM, and PI. These results provide theoretical contributions by integrating AI, DM, e-WOM, and PI into a comprehensive model, highlighting their synergistic effects in social commerce environments. From a managerial perspective, businesses should prioritize AI-driven automation, targeted digital marketing, and e-WOM optimization to enhance consumer engagement and drive purchasing behavior. As social commerce evolves, leveraging technology-enhanced marketing strategies will be essential for businesses to maintain competitive advantage and consumer loyalty.